CpG-Recoding in Zika Virus Genome Causes Host-Age-Dependent Attenuation of Infection With Protection Against Lethal Heterologous Challenge in Mice - Trus, Ivan; Udenze, Daniel; Berube, Nathalie; Wheler, Colette; Martel, Marie-Jocelyne; Gerdts, Volker; Karniychuk, Uladzimir (Frontiers in Immunology, 2020)
Experimental increase of CpG dinucleotides in an RNA virus genome impairs infection providing a promising approach for vaccine development. While CpG recoding is an emerging and promising vaccine approach, little is known about infection phenotypes caused by recoded viruses in vivo. For example, infection phenotypes, immunogenicity, and protective efficacy induced by CpG-recoded viruses in different age groups were not studied yet. This is important, because attenuation of infection phenotypes caused by recoded viruses may depend on the population-based expression of cellular components targeting viral CpG dinucleotides. In the present study, we generated several Zika virus (ZIKV) variants with the increasing CpG content and compared infection in neonatal and adult mice. Increasing the CpG content caused host-age-dependent attenuation of infection with considerable attenuation in neonates and high attenuation in adults. Expression of the zinc-finger antiviral protein (ZAP)—the host protein targeting viral CpG dinucleotides—was also age-dependent. Similar to the wild-type virus, ZIKV variants with the increased CpG content evoked robust cellular and humoral immune responses and protection against lethal challenge. Collectively, the host age should be accounted for in future studies on mechanisms targeting viral CpG dinucleotides, development of safe dinucleotide recoding strategies, and applications of CpG-recoded vaccines.